How Do Technology-Enhanced Learning Tools Support Critical Thinking? - Le, Nguyen-Thinh (Frontiers in Education, 2019)
This paper reviews existing computer-supported learning systems that have claimed to adopt Socratic methods for enhancing critical thinking. Several notions of Socratic methods are differentiated: the critical thinking framework of Paul and Elder, the classic Socratic method, the modern Socratic method, and the neo-Socratic group discussion method. Three lessons are highlighted. First, the development of learning systems specifically supporting critical thinking is still lacking Thus, further research in this area is urgent. Second, most developed computer-supported learning systems claim to support Socratic approaches (e.g., Socratic tutoring) which are based on human tutoring strategies and do not show a systematic Socratic method. Third, the classic Socratic method has not been applied in any reviewed learning system.